Influence of SCN− moiety on CH3NH3PbI3 perovskite film properties and the performance of carbon-based hole-transport-layer-free perovskite solar cells - Prasan, Primprapha; Aunping, Namfon; Chanlek, Narong; Kumlangwan, Pantiwa; Towannang, Madsakorn; Klangtakai, Pawinee; Srepusharawoot, Pornjuk; Thongnum, Anusit; Kumnorkaew, Pisist; Jarernboon, Wirat; Pimanpang, Samuk; Amornkitbamrung, Vittaya (My University, 2022)
CH3NH3PbI3 perovskite films were prepared via a hot-casting method using six different CH3NH3I, PbI2 and Pb(SCN)2 solutions. Surface morphology of perovskite films with low SCN− dopant levels (0.0625 M and 0.125 M Pb(SCN)2) showed smooth surfaces and large grain sizes. However, with the high SCN− dopant levels (0.1875 M and 0.25 M Pb(SCN)2), rough surfaces were produced with pinholes. The crystal of pure CH3NH3PbI3 (0 M Pb(SCN)2) film is a tetragonal perovskite structure. XRD spectra of all five Pb(SCN)2 added films show the present of CH3NH3PbI3 films and the additional peak at 12.66°. Rietveld refinement analysis reveals that the Pb(SCN)2 addition causes the second phase PbI2 formation along with the tetragonal MAPbI3 perovskite film rather than the CH3NH3Pb(SCN)xI3-x perovskite formation. The carbon-based hole-transport-layer (HTL)-free perovskite (from 0.0625 M Pb(SCN)2 dopant) solar cell is the optimal ratio in generating a promising cell efficiency, 6.34%, with a good efficiency retention of 79.43% after 30 days of testing in comparison to a pure CH3NH3PbI3 (0 M Pb(SCN)2 dopant) perovskite solar cell with an efficiency retention of only 26.92%. The great stability of the Pb(SCN)2 added perovskite solar cells is attributed to the PbI2 layer covered MAPbI3 grains blocking oxygen and/or water molecules from degrading MAPbI3 perovskite.